Biochar addition enhances remediation efficiency and rapeseed yield in copper-contaminated soil - Sheng, Ziwei; Luo, Tao; Wang, Linjie; Chen, Min; Ma, Bingbing; Liu, Lijun; Wang, Bo; Kuai, Jie; Wang, Jing; Zhao, Jie; Xu, Zhenghua; Zhou, Guangsheng (Frontiers in Plant Science, 2024)
Soil contamination with copper (Cu) threatens ecological security and human health. Rapeseed demonstrates potential in remediating copper-contaminated soil, and biochar-assisted phytoremediation is increasingly being employed to improve remediation efficiency. However, the combined application of them has not been thoroughly studied in terms of the synergistic effects and the mechanisms of their interaction. In this regard, this study conducted a pot experiment to evaluate biochar-assisted remediation under Cu-contaminated soil with varying biochar application rates; Furthermore, the plant physiological mechanism and soil physicochemical properties involved in the biochar-rapeseed system was explored. Our results showed that the exchangeable pool of copper in soil decreased by 10.0% and 12.3% with adding 5% biochar (BC1) and 10% biochar (BC2) relative to control (BC0), respectively, prior tobefore rapeseed cultivation. The rapeseed cultivation for one season further reclaimed 4.9%, 9.0%, and 13.6% of the available copper in this soil by root extraction under the BC0, BC1, and BC2 treatments, respectively. The overall copper concentration in plants decreased by 23.7% under BC2 and 13.3% under BC1 compared to BC0. However, the plant's dry biomass at BC1 and BC2 treatments increased by 1.7-fold and 2.7-fold relative to BC0, which offset the negative impact of the decreased copper concentration on phytoremediation. Physiological analysis showed adding 10% biochar decreased the MDA content by 36% in the leaf and 49% in the root, compared to BC0. The transmission electron microscopy for cell wall ultrastructure in root tips showed that biochar addition in Cu-contaminated soil increased the mechanical strength of the cell wall, explicitly increasing the thickness of the secondary cell wall. Further cell wall components analysis revealed a remarkable increment of the pectin content in BC2 relative to BC0, increased by 56% in the leaf and 99% in the root, respectively. Additionally, 10% biochar application led to a roughly 2-fold increase in seed yield via ameliorating the soil physicochemical properties and increasing the rapeseed growth. These findings offer insights into synergistic rapeseed-biochar use for Cu-contaminated soil remediation.